A catalogue of Indian Gelechiidae Stainton, 1854 (Lepidoptera: Gelechioidea) - D, Nandhini; R., Shashank P.; Joshi, Rahul; Reddy, Karthik M. (Zootaxa, 2024)
We present an annotated catalogue of the Lepidoptera family Gelechiidae of India, comprising 351 species in 80 genera, encompassing seven subfamilies. The Indian fauna represents 7.47% of global gelechiid species diversity (i.e., 4,700 species in 500 genera). Among the seven subfamilies, Dichomeridinae is the best represented (122 species in four genera), followed by Gelechiinae (76 species in 38 genera), Anacampsinae (70 species in 16 genera), Thiotrichinae (49 species in five genera), Anomologinae (26 species in nine genera), Apatetrinae (seven species in seven genera), and Physoptilinae (single species). Information on type locality, type repository, synonyms, geographical distribution, hosts, natural enemies, and references to illustrations are provided. We also reviewed the history of descriptive work on the Gelechiidae of India, and resolved ambiguities regarding the current status of some species.